Advance care planning in New Zealand: A qualitative study of the motivators and barriers to uptake. (7th November 2020) - Brown, Wendy; Baken, Donald; Stephens, Christine
Abstract: Objective: As a follow‐up to the first national survey of advance care planning uptake in New Zealand, which demonstrated a low level of plan completion, this study seeks to better understand the motivators and barriers associated with uptake. Methods: Using a qualitative approach and a purposeful sampling method, nine interviewees participated in semi‐structured interviews exploring in further depth their knowledge, attitudes and activities in relation to planning for end‐of‐life care. Thematic analysis was applied to the transcripts and several key themes identified. Results: The five key themes were Knowledge of Advance Care Planning; Incomplete Planning; Relational Autonomy; Focus on Family; and Still Time to Plan. Conclusion: A stepped process to encourage planning uptake is suggested, with legal and financial steps preceding the making of more personal values–based decisions salient to a serious diagnosis.